Membangun Kinerja Hijau melalui Green Organizational Culture dan Green Human Resource Management: Bukti Empiris dari Dealer Otomotif di Indonesia - Serli Lestari; Debi Septiani (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This research examines the effect of Green Organizational Culture (GOC) and Green Human Resource Management (GHRM) on Green Performance (KH) at the authorized dealer of Toyota TAA Palembang. Within the context of the automotive industry facing increasing pressure to adopt environmentally sustainable practices, GOC and GHRM serve as critical determinants in enchancing GP within the organization. This study employed a quantiative approach using a a survey method with a quesionaire administrated to all 46 employees of the authorized dealer Toyota TAA Palembang, applying a total sampling (sensus) technique. The findings demonstrated that both GOC dan GHRM have a positive and significant effect on GP. Notably, the results revealed that GHRM exerts a dominant influence compared to GOC on GP. Simultaneously, both variables collectively explained 52.4% of the variance in GP. This study offers valuable insights for automotive dealership management to develop strategic GHRM interventions, particularly through technical training on hazardous waste handling and the implementation of reward systems based on GP achievement, in order to enhance organizational competitiveness and ensure compliance with environmental regulations in Indonesia.